Assessing the effects of Cry1C rice and Cry2A rice to Pseudogonatopus flavifemur, a parasitoid of rice planthoppers - Jun-Ce Tian (Nature Portfolio, 2017)
Abstract Transgenic rice producing insecticidal proteins from Bacillus thuringiensis (Bt) could help protect the plants from damage by lepidopteran pests. However, one concern is the potential of Bt rice to harm non-target natural enemies, which play a vital role in pest control. In the present study, the potential effects of Cry1C rice and Cry2A rice on different life-table parameters and population dynamics of Pseudogonatopus flavifemur, a parasitoid of rice planthoppers, were evaluated under laboratory and field condition. The exposure of P. flavifemur to plant-produced Bt proteins was also analyzed. Results indicated that direct feeding on rice plants was the main exposure pathway of P. flavifemur to the Cry1C and Cry2A proteins. No significant difference on the development, survival, longevity, fecundity, and prey consumption of P. flavifemur was detected over two generations between the Bt and non-Bt rice treatments. Furthermore, the population dynamics of P. flavifemur were not affected by Cry1C rice and Cry2A rice. In conclusion, the tested Cry1C rice and Cry2A rice do not appear to harm the parasitoid P. flavifemur.